(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
In this article, issues related to the moral importance of peacekeeping, its influence on the spiritual image of society, and their role and necessity in ensuring the development and stability of society in the context of globalization are discussed based on the teachings of Islam, Christianity, Aristotle, Pharobii, H. Vamberi, B. Russell, A. Einshtein, E.Giddens, P. Byuchanan, A.Sher, Sh.Mirziyoev, as well as the issues of the application of pacifist ideas in the development of society are analyzed. Studying the causes and analyzing the consequences of threats to the stability of regions and states, civil peace, and social well-being are noted as important factors of spiritual and moral development. Global problems of the present time, that is, ensuring peace on earth, preventing thermonuclear conflict and establishing a just international economic-political new order; effective environmental protection; achieving a balance between the number and composition of the population and the creation of material and moral values; reliable provision of necessary food and energy resources to the population of the land; solutions to problems such as the eradication of hunger, poverty and backwardness are explored.